2010 17th IEEE International Conference and Workshops on Engineering of Computer Based Systems 2010
DOI: 10.1109/ecbs.2010.38
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Architectural Framework for Agile Software Development

Abstract: One of the ideas of agile software development is to respond to changes rather than following a plan. Constantly changing businesses result in changing requirements, to be handled in the development process. Therefore, it is essential that the underlying software architecture is capable of managing agile business processes. However, criticism on agile software development states that it fails to pay attention to architectural and design issues and therefore is bound to engender suboptimal design-decisions.In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…However, it is utilized mostly in small or medium-sized projects [22]. Investigating the efficiency of XP due to its ever-increasing popularity is one of the great challenges in software engineering research studies [23].…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, it is utilized mostly in small or medium-sized projects [22]. Investigating the efficiency of XP due to its ever-increasing popularity is one of the great challenges in software engineering research studies [23].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For many software projects, any change of the requirements will lead to design adjustment. AM is proposed as a solution to problems resulting from an unpredictable world [3], which encourages requirements change, so that the architecture must be adjustable. The new release plan and iteration plan in each phrase will cause architecture to be evolved.…”
Section: Introductionmentioning
confidence: 99%
“…The model is robust against changes due to new requirements. We have termed this "architecture agility" in [13] and shown that the space-based architectural style helps to avoid costly architecture limiters or even breakers. The Peer Model extends this idea by not only considering passive data, but also modeling the active part, i.e.…”
Section: Related Workmentioning
confidence: 99%